Experimental Simulation of Clinical Borderline Situations in Temporal Bone Specimens After Ossiculoplasty. Issue 1 (January 2018) - Jakob, Till F.; Kromeier, Jan; Baumann, Tobias; Pfeiffer, Jens; Neudert, Marcus; Laszig, Roland; Zahnert, Thomas; Offergeld, Christian
Abstract : Objectives: One reason for insufficient hearing improvement with a distinct air–bone gap after ossiculoplasty with implantation of partial or total ossicular replacement prostheses can be the dislocation or minimal shifting of the prosthesis. The aim of this study was the simulation of common clinical borderline situations with minimal shifting of the prosthesis in temporal bone specimens after ossiculoplasty. It was furthermore the goal to identify these specific situations through imaging by cone beam computed tomography (cbCT) and direct visual inspection using the operation microscope. Additionally, the functional status was evaluated using laser-Doppler vibrometry (LDV). Design: We used a total of four temporal bone specimens for this study. A reconstruction with a partial ossicular replacement prostheses was performed in three specimens and with a total ossicular replacement prostheses in one specimen, with good initial acoustic properties. Subsequently, one specific type of prosthesis failure was simulated in each specimen, respectively, by minimally shifting, tilting, or bending the prostheses from their initial positions. These changes were introduced step-by-step until a borderline situation just short of complete acoustic decoupling was reached. Each step was examined using both LDV and cbCT and observed through the operation microscope. Results: LDV was able to quantify the mechanic function of the ossicular chain after most of the manipulation steps by demonstrating the effect of any shifting of the prosthesis on the middle ear transfer function. However, in some situations, the middle ear transfer function was better with a visually more advanced failure of the prosthesis. In addition, cbCT showed most of the steps with excellent resolution and was able to delineate changes in soft tissue (e.g., cartilage covering). Conclusion: cbCT seems to be a promising imaging technique for middle ear problems. As cbCT and LDV exhibited slightly different advantages and disadvantages regarding the demonstration of borderline situations, the combination of both techniques allowed for a more precise evaluation of middle ear reconstructions. Knowledge of the specific characteristics of these methods and their possible combination might help otologists and otosurgeons to refine indications for revision surgery and improve their personal patient counseling.